RESEÑA de : Martín, José Luis. Enrique IV de Castilla : Rey de Navarra, Príncipe de Cataluña. Hondarribia : Ed. Nerea, 2003 - López Pita, Paulina (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2003)
-